Evaluasi Sistem Proteksi Petir Pada Tower Pt. Sampoerna Telekomunikasi Indonesia (Ceria) Pekanbaru - Febriani Syafran Putri; Eddy Hamdani (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
Lightning occurs because there is a difference of potential between the cloud and the earth or by other clouds. Lightning caused a lot of harm to people and damage to the equipment. Some places with the high rate of lightning strikes (frequency and intensity) of being the first priority in the use of the installation of lightning protection. Tropical countries like Indonesia generally have a high lightning day each year, including in the area of Pekanbaru. This paper proposes to evaluate lightning protection system in PT. Sampoerna Telekomunikasi Indonesia (Ceria) Pekanbaru. Improvement of lightning protection system is made through a Rolling Sphere Method. The result of the data shows that the lightning protection system in PT. Sampoerna Telekomunikasi Indonesia (Ceria) Pekanbaru was already capable of protecting the Base Station Transceiver (BTS) from lightning strikes. This results is proven to indicate that lightning protect is improved.Keywords: lightning protection system, Rolling Sphere Method, lightning protection system in PT. Sampoerna Telekomunikasi Indonesia (Ceria) Pekanbaru